Sustainable Development of Wadi Houran- Western Iraqi Desert - Abdulhameed., Isam; Ahmed, Muneer; Hamed, Waleed; Ghan, Emad; Naif, Rasha; Hamad, Rasmi.; Mutar, Hasan; Ibrahem, Muthanna; Fayyadh, Abed; Alhadeethi, Isam; ALmafrchi, Kamal; Kamel, Ammar; et al. (Iraqi Journal of Civil Engineering, 2022)
Wadi Houran is one of the largest valleys in Iraq. Although it is discharging billions of rainfall water over/during many years to Euphrates river, it’s almost devoid of agricultural investment. The current study aims to focus on this important valley water resource and study the possibility of constructing a series of small dams to store rainfall water and planting forestry and establishing a natural reserve that is able to sustain and improve ecology system. Target area of 4000 km2 is selected in the midstream of the valley. In general, it is about one billion m3 of rainwater flowing to Euphrates River during some years with yearly average values about 400 Mm3. Four dams were constructed to store about 46 Mm3 of rainwater. It is possible to construct small-dam-series of optimal height and location to expand the rainwater harvesting and groundwater recharging. A Current study was done and aimed to establish of oases and natural reserves in order to improve climate conditions, minimize the dust and CO2, mitigation of summer high temperature and decrease the soil erosion due to torrents. This study recommended constructing 13 optimal height dams that store about 303 Mm3 of water, and increase the water surface area of reservoirs in this valley from 15 to 90 km2which leads increase the water volume that is recharging ground water from 4.7 Mm3 to 28 Mm3 per year.